Trends in Political Professionalisation Research: Bibliometric Mapping of Published Articles in the Scopus Database - Sauki, Muhammad; Hidayat, Rahmad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
Political professionalisation is essential in developing more structured, efficient, and transparent political practices oriented toward the broader public interest. However, the process also faces challenges such as potential elitism and alienation of politicians from the general public. Using the Bibliometrix RStudio software, this review presents trends and patterns in political professionalisation research from 57 articles in the Scopus database, published between March 1997 and April 2024. There is a significant upward research trend, with 5.27% annual publication growth on the issue. The authors found four primary research streams in the study of political professionalisation, each integrating distinct thematic categories: (1) the nature of political professionalisation focuses on the fundamental characteristics of political professionalisation, including its core substance and the evolving profile of career politicians; (2) political professionalisation strategies and capacity examines the mechanisms through which professionalisation occurs, covering the legislative role, political communication and campaigns, and the institutionalisation of political parties; (3) the adoption and diffusion of political professionalisation highlights shifts in politician recruitment patterns and the impact of country size on professionalisation processes; (4) the implementation and impact of political professionalisation assess the consequences of these transformations, providing insights into their broader political implications. Several areas still require further investigation based on the 56 questions identified. By filling these gaps, future research will provide a more holistic view of political professionalisation in an increasingly complex and changing political context and enhance the effectiveness and inclusiveness of political systems worldwide.